ANALISIS DAYA DUKUNG PONDASI TIANG DENGAN POTENSI PENAMBAHAN BEBAN PADA STRUKTUR BANGUNAN (STUDI KASUS: GEDUNG REKTORAT UNIVERSITAS PANCA BHAKTI PONTIANAK) - Maria Esijunianti Abik; Yufiansyah; Irvhaneil (Jurnal Teknologi Infrastruktur, 2022)
The Chancellor's Building of Panca Bhakti University is a building that will later be used and functioned as a place of work for the Rector and his staff. This building uses a type of pile foundation where this type of foundation is a strong foundation and is able to transmit the load of the structure above it to the soil layer below it. Pile foundations are construction parts made of wood, concrete, and or steel that are used to continue ( transmits) surface loads to lower surface levels in the soil mass. From the calculation results obtained on the foundation with a size of 25x25 cm, the load that works on the foundation before there is an additional load on the foundation type P2 is 59.5123 tons, P4 is 219.4528 tons, P5 is 136.6882 tons, P6 is 286.6502 tons , P8 of 260.5605 Tons. The load that works after there is an additional load on the foundation type P2 is 59.5290 tons, P4 is 220.1393 tons, P5 is 137.2088 tons, P6 is 288.6334 tons, P8 is 263.4673 tons. The carrying capacity of the single pile obtained from the results of the sondir test data before and after there is an additional load obtained on the P2, P4, P5, P6, P8 foundation types is 131.454 tons. The carrying capacity of the pile group before and after there is an additional load on the foundation type P2 is 246,1808 tons, P4 is 492,1637 tons, P5 is 643,4673 tons, P6 is 730,358 tons, P8 is 1022,186 tons changed to type P2 is 246,1808 tons, P4 is 492,1637 tons, P5 is 643,4673 tons, P6 is 730,358 tons, P8 is 1022,186 tons.